Mobile Multimedia Broadcasting Standards - Luo, Fa-Long (Springer, 2017)
This volume provides a comprehensive and cohesive compilation of multi-standards and systems for mobile multimedia broadcasting. The material includes coverage of the basic principles, algorithms, and design trade off as well as examples of software and hardware that have been implemented at the system level.